Enhancement of the energy and exergy analysis capabilities of the yoghurt process: a case study of the dairy industry - Oztuna Taner, Oznur (Frontiers in Sustainable Food Systems, 2024)
This study provides a comprehensive analysis of the thermal and exergy characteristics of a dairy plant that produces yoghurt. This study aims to perform a comprehensive analysis of the thermal and exergy aspects of a dairy facility that produces yoghurt. This study also seeks to improve the accuracy of the results by evaluating the reliability of the energy and production data. A comprehensive analysis of energy and exergy is utilized to enhance the yoghurt production process. Moreover, the Grassmann-Sankey diagram is employed to produce a map of energy density. The process’s energy and exergy efficiencies were assessed by taking into account the enhancements and alterations made in addition to the existing implementations. Analysis of the yoghurt production process revealed that the total energy input was 113.9 [kW], the total energy output was 72.05 kW as well and the energy efficiency was 63.3%. The exergy input and output for the yoghurt production process were calculated to be 48.95 [kW] and 29.77 [kW], and the exergy efficiency was determined to be 60.8%. This study is expected to promote the growth of livestock and agriculture in the energy sector, and is forecasted to act as a catalyst for future research. This study, which is the first of its kind in the region and is expected to stimulate further research, reveals that improving energy efficiency and conservation in the production of yoghurt products enhances the factory’s overall energy efficiency.